Efectos de la capacitación en el personal de la construcción: caso Ecosur Ecuador - Chimborazo Villacis, Katherin Adriana (2022)
Training is a mechanism adopted by different companies to strengthen the skills and knowledge of their personnel through courses, seminars, or other learning methods. However, most of the entities dedicated to personnel training obtain the results from user comments or using tests at the end of the training; these data are helpful when assessing the satisfaction of the training, but they do not measure the long-term effects. It is essential to know if there are changes in the participant's habits at the end of the course, or if it was only exciting and the time and money invested are quickly lost in everyday life. Consequently, this work shows a systematic process with a documentary review, the design, and the application of the survey. In addition, an on-site visit to observe and interview the personnel for the development of this research, applying quantitative techniques to identify what was achieved with the confined masonry training given by the EcoSur Ecuador network to the construction personnel, analyzing the contents and methodology used in the courses. To achieve the objective, we worked with a sample of 20 people belonging to the association of builders of the city of Buena Fe, province of Los Ríos, to apply a knowledge survey. The Researcher interviewed the board of directors of the association for a study of opinions and thus determined the effect caused by the training.